0756 Focal Interview of Sleep (FIOS) for Children: Preliminary Psychometrics. (12th April 2019) - Patriarca, Guadalupe; Ricketts, Emily; Milbert, Melissa; Trubnick, Laura; Forbes, Erika; Silk, Jennifer; Ladouceur, Cecile; Siegle, Greg; Ryan, Neal; Harvey, Allison; Dahl, Ronald; McMakin, Dana L
Abstract: Introduction: Sleep-related problems are pervasive among youth with psychiatric symptoms, heterogeneous in nature, and vary by frequency, intensity, duration, and impairment. This poses a challenge for measurement of sleep problems in these populations. Although there are well-validated self-reports of sleep functioning in pediatric samples, we presently lack validated clinician-rated interviews of sleep-related problems for youth. Therefore, we developed and validated a multidimensional clinician-administered interview for sleep-related problems that are common in youth with psychiatric symptoms. Methods: Participants were 46 youth (ages 9-15; M = 11.60; SD =1.63) from sleep trial (Sleeping Tigers) delivered through the Child Anxiety Treatment Study (CATS). An independent evaluator administered the Focal Interview of Sleep (FIOS), assessing the frequency, duration and intensity of seven sleep problems (e.g., trouble going to bed, trouble falling asleep, sleepy, tired, irritable, etc.) at baseline and post-treatment. Three FIOS scores, including Number of Sleep Problems, Impairment and Total Score were derived from these ratings. Youth completed actigraphy, sleep diary, and the Sleep Self-Report; and parents rated youth sleep (i.e., Children's Sleep Habits Questionnaire), and behavior and emotions (i.e., Child Behavior Checklist 6-18). Parents and youth also completed the Mood and Feelings Questionnaire and Screen for Child Anxiety and Related Emotional Disorders. Results: Interrater reliability was excellent (ICC=.75-1.00) for FIOS Duration, Frequency and Intensity scores by sleep problem type. Internal consistency was mostly excellent (range α = .65 to .94) for sleep problems. FIOS scores demonstrated strong treatment sensitivity. Convergent validity was fair for parent- and child-report of youth sleep, and sleep quality per sleep diary. There was limited support for discriminant validity, as evidenced by non-significant Fisher's R to Z transformation for the difference between FIOS Total and behavioral/emotional problems, anxiety and mood. Baseline FIOS predicting one-year sleep outcomes was non-significant. Conclusion: Findings suggest the FIOS is a psychometrically sound clinician-rated measure of sleep-related problems in youth with psychiatric symptoms. Future research can focus on discriminant and predictive validity, as well as replication in larger, more heterogeneous samples. Support (If Any): National Institute of Mental Health: MH080215